Pengaruh Kompetisi, Corporate Governance, terhadap Risk Disclosure (Studi Kasus pada Bank BUMN) - Mike Kusuma Dewi; Elsa Meirina (Jurnal Kajian Akuntansi dan Auditing, 2021)
This research is a quantitative research in which the problem solving model and analysis is carried out by examining the influence between the independent variables. Thus the purpose of this study is to see how the influence of business competition in the banking world along with Good Corporate Governance on Risk Disclosure at state-owned banks. This research was conducted on 4 research objects of state-owned banks in Indonesia which were analyzed using data processing tools, namely SPSS ver.23. The research was conducted from 2012 to 2019. The results of the above research can be concluded that the independent variable (H1) has a significant effect on risk disclosure. Meanwhile, other independent variables, namely the size of the board of commissioners (H2) and the composition of the independent board of commissioners (H3), have no significant effect on risk disclosure Keywords : Competition, Corporate Governance, Risk Disclosure